Czech Republic : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2012)
This paper presents detailed assessment of the Czech Republic's compliance with Basel Core Principles (BCPs) for effective banking supervision. Many earlier weaknesses have been addressed, either through domestic measures or by implementing European Union-wide rules and regulations. An overarching weakness is the insufficiency of staff resources for supervision. The nonfinancial corporate sector's financial indicators are relatively sound, but the macroeconomic uncertainty weighs on the prospects. Property prices have substantially declined since 2008 reflecting subdued demand.